2023
DOI: 10.1117/1.nph.10.1.015008
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal in vivo imaging of perineuronal nets

Abstract: Significance: Perineuronal nets (PNNs) are extracellular matrix structures implicated in learning, memory, information processing, synaptic plasticity, and neuroprotection. However, our understanding of mechanisms governing the evidently important contribution of PNNs to central nervous system function is lacking. A primary cause for this gap of knowledge is the absence of direct experimental tools to study their role in vivo.Aim: We introduce a robust approach for quantitative longitudinal imaging of PNNs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Live brain imaging of the PNN structural and functional dynamics has remained absent until very recently, although longitudinal in vivo imaging techniques for brain cells and some ECM components have been around for a while [175,182,183]. To that end, a highly promising methodology-oriented study has reported longitudinal in vivo imaging of the PNN using live brain two-photon microscopy on a mouse barrel cortex [89]. The PNN was stained by intracranial injection of fluorescent WFA.…”
Section: Future Methodological Perspective For Pnn Microscopy 81 Mult...mentioning
confidence: 99%
See 1 more Smart Citation
“…Live brain imaging of the PNN structural and functional dynamics has remained absent until very recently, although longitudinal in vivo imaging techniques for brain cells and some ECM components have been around for a while [175,182,183]. To that end, a highly promising methodology-oriented study has reported longitudinal in vivo imaging of the PNN using live brain two-photon microscopy on a mouse barrel cortex [89]. The PNN was stained by intracranial injection of fluorescent WFA.…”
Section: Future Methodological Perspective For Pnn Microscopy 81 Mult...mentioning
confidence: 99%
“…[50] (×20), [51]; [89] WFA, Aβ (Amylo-Glo), CD68, Iba1, Thioflavin-S, PV, Aggrecan, Crtl1, GAD65/67, vGlut1, Cat-301, calretinin, MAP2, VGAT, brevican Schizophrenia, bipolar disorder [42] (×20/0.5; ×63/1.4); [99]; [100] (×20/0.5); [101] (×20; ×40) WFA, PV, HNK-1, S100-β, CS56, MMP9, 8-oxo-dG, CD68, Iba1 Substance use disorder [102] (×20/0.7; ×63/1.4); [103] (×20/0.75; ×20/0.7); [104] (×40); [105] (×63/1.4); [106] (×40), [107]; [32] (×20/0. Hibernation-like state [113] AI-assisted Normal brain [34,36] WFA, parvalbumin…”
Section: Confocal Microsopymentioning
confidence: 99%
“…The removal of cortical PNNs reverses PV cell maturation and enhances adult plasticity, offering the potential for brain repair (12). Local parenchymal injections of chondroitinase ABC (ChABC) enzyme degrade CSPGs resulting in rapid yet transient PNN removal, with PNN recovery beginning by 6 days and reaching at least 80% by 3 weeks (7,13,14). In rodents, ChABC has been used in the primary visual cortex (V1) to restore binocular vision in models of amblyopia (15), and in the spinal cord and peripheral nerves to treat injuries via its action on glial scars (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific mechanism of PNN in spinal cord injury remains unclear and needs to be further explored and studied. A recent study identified that the average area under the curve (AUC) of PV+/PNN+ was significantly larger than that of PV+/PNN‐ through in vivo two‐photon modified imaging, 16 which confirmed the statement that PNN is the key factor to maintain the high‐frequency discharge of Parvalbumin interneuron (PV‐IN) 17 . The relationship between PNN and PV‐IN and their cascade reaction has made significant progress in the studies of brain injury, 18 optic nerve injury, 19,20 epilepsy, 21 and psychiatric disorders 22,23 .…”
Section: Introductionmentioning
confidence: 99%